THAT APPLICATION OF FUNDS STATEMENT. - Castenholz, W. B. (The Accounting Review, 1956)
Abstract So there may be no misunderstanding of my thesis, I have (1) used the term "capital fund" to indicate the total net capital or resources available for the operation of a business; (2) segregated this "capital fund" into its two component funds, namely "working capital fund" and "fixed capital fund"; (3) stated, therefore, that "capital funding" ordinarily occurs only from net profits and the addition of new capital; (4) held that the internal operations of a business frequently involve the conversion of working capital into fixed capital and vice-versa; that these should be called "conversion funding" because they do not affect the "capital fund," but (5) that all of these funding operations be aptly described in the Application of Funds Statement, so that the reader may clearly see how they affect working capital; finally, that the term "non-funding operations" is misleading and incorrect because these are clearly operations between the two component funds which make up the total capital fund of a business; they are funding operations, hence the term "conversion funding" is recommended.